Skeletal Muscle Metastasis to Vastus Lateralis from a Urothelial Carcinoma: A Case Report and Review of Its Diagnosis and Management - A. M. Mainwaring; H. Wells; T. Banks; T. Ellul; P. Bose (Case Reports in Urology)
Bladder cancer is a common genitourinary tract malignancy. Urothelial carcinoma is the most frequent type of bladder cancer and it commonly metastasises to lymph nodes, bone, lung and liver by a haematogenous route. Skeletal metastases are very rare and are usually present in patients with advanced metastatic disease. We present an unusual case of a 71-year-old male with a urothelial carcinoma metastasis to the vastus lateralis muscle 3 months following a cystoprostatectomy for muscle invasive bladder cancer.